Transporte acoplado de calor, umidade e sal em estruturas de concreto - Ribas, Rhayssa Maryell Marra (2021)
Concrete is a material widely applied in civil construction and for this reason its deterioration can cause economic and environmental damage. The corrosion of concrete can occur in several ways: due to mechanical stresses, climatic changes, temperature changes and chemical attacks such as the transposition of salts into concrete pores. In addition to accelerating the degradation of the steel frame, this last process can concentrate the salts in some points, which crystallize, increasing the internal pressure in the pores and causing fissures and cracks, making the whole structure more susceptible to other agents of deterioration. Thus, the objective of this work is to analyze numerically the coupled transport of moisture, heat and salt in the porous medium of concrete. Initially, the governing equations were modeled and then discretized using the finite volume method. For the solution of the system of algebraic equations was used the Multi Tri-Diagonal Matrix Algorithm (MTDMA), which allows the simultaneous resolution of the 3 governing equations. The proposed model was verified through comparisons with a model available in literature. Other simulations were performed to analyze the influence of humidity and temperature on the transport of salt. From the results obtained, it is possible to observe the importance of the imbibition and drying process for the transport of salt, as well as the influence of temperature in this analysis.